O escudo de Perseu a refletir a imagem de Medusa: o processo formativo autopoiético em narrativas autobiográficas de estudantes de Pedagogia - Visentini, Lucas (2014)
This master thesis is about the autopoietic development process of undergraduate students of pedagogy from Universidade Federal de Santa Maria (UFSM), who were studied by us in this thesis. The main objective was to search the senses wire weaved in the autopoietic development process of undergraduate students of pedagogy from Universidade Federal de Santa Maria (UFSM) and study the meanings built by the students that link them to the teaching profession. The research subjects of this study accepted to share with us his experiences by the Termo de Consentimento Livre e Esclarecido (TCLE). It s a qualitative research considering the autobiographic perspective and the methodological process involved individual narratives interviews, which one were recorded, transcribed and analised by the Análise Textual Discursiva (ATD), according to Roque Moraes (2003). The theories of this study were built by these concepts: autopoiese (MATURANA & VARELA, 2001; 2010); processo identitário docente (ISAIA, 2006); narrativas (JOSSO, 2004; 2010); identidade profissional docente (ISAIA, 2006); narrativas de Si (ABRAHÃO, 2006); investigação narrativa (ISAIA, 2006); memória educativa (FERNANDES, 2006); formação inicial (CUNHA, 2006); processos formativos (OLIVEIRA, 2006); percurso vital (MACIEL, 2006); trajetória, trajetória profissional e trajetória de formação (ISAIA, 2006) e ambiência (MACIEL, 1995; 2000; 2006; 2009; 2010). We hope, with this search, to contribute with education and teacher training of basic education, considering the theories about the autopoietic development process of undergraduate students of pedagogy, regarding the meanings built by them that link those students to the teaching profession.